Preparação e caracterização de coacervatos e vidros a base de fosfato, dopados com európio - Dias Filho, Francisco Audisio [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
O processo de coacervação, oriundo da interação entre soluções de polifosfato de sódio(sal de Graham) e cloreto de cálcio, foi estudado pela luminescência do íon Eu3+. Entende-se por coacervação uma separação de fases líquido-líquido. Espectros de emissão e excitação e a eficiência quântica de emissão do estado excitado 5D0 do íon Eu3+mostram ser extremamente sensíveis a mudanças estruturais na primeira esfera de coordenação do íon Eu . Os parâmetros luminescentes do íon Eu3+ são intensificados na presença do polifosfato. A interação do Eu3+ com o polifosfato foi explicado levando em conta modelos estruturais usados para estudar vidros a base de fosfato. Os modelos estruturais usados para entender a interação Eu3+-polifosfato também foram utilizados para entender o papel do eletrólito no processo de coaservação. A comparação dos resultados de luminescência com os modelos estruturais dos vidros a base de fosfato, mostram que existe uma concentração crítica responsável pela coacervação. A capacidade da solução aquosa de polifosfato de sódio agir como agente coordenante, estabilizante e dispersante mostrou ser interessante na preparação de coacervatos incorporados com CdS, WO3, rodamina e Er2O3. O efeito de confinamento quântico foi observado nos coacervatos com CdS. Compósitos, inéditos, de polifosfato-siloxanos...

The liquid-liquid phase separation occurring in polyphosphate solutions, so-called coacervation process is studied by luminescence of Eu3+. The coacervation studied here was obtained by controlled addition calcium chloride of sodium polyphosphate (Graham Salt) solution. Spectrocopic parameters like 5D0 quantum yield and emission and excitation spectra have been monitored in different solutions and were shown to be extremely sensitive to structural changes occurring at the Eu3+ first coordination shell. The luminescence parameters are enhanced in the presence of polyphosphate, and the Eu3+-polyphosphate interaction was explained taking into account structural models used in the study of polyphosphate glasses. The dependence of the coacervation on the electrolyte concentration was also explained by structural models. A critical concentration was identified from the spectroscopic study showing the probe characteristics of the Eu3+ ions. The coordinating, stabilizing and dispersing power of polyphosphate in solution showed to be interesting to preparation of coacervates incorporated with CdS, WO3, rhodamine and Er2O3. The quantum size effect was observed to CdS in coacervates. A new polyphosphate-siloxanes composite was obtained from polyphosphate solutions and aminopropyl modified silane. These composites were characterized by P, Si and C NMR, vibrational spectrocopy and Eu3+luminescence. Enhanced luminescence properties were observed compared to polyphosphate precursor solution. Glasses in the pseudo-binary system NaPO3-Nb2O5 were prepared and characterized. Glasses displaying a wide range of Tg(Glass transition temperature) values, from 470 to 700ºC, were obtained. Colors of the final products could be controlled by the melting conditions, wich leads to reduction of Nb5+ to Nb4+. This process was corroborated by absorption and EPR. In order to produce planar waveguides on the glass surface...(Complete abstract click electronic access below)
Keywords: Vidros; Compostos de coordenação; Química inorgânica